Assessing flow limitation in patients with stable coronary artery disease. (20th October 2016) - Townend, Jonathan N; Ludman, Peter F; Doshi, Sagar N; Khan, Hamid; Calvert, Patrick A
Abstract : Has simple coronary angiography had its day?